Cardiac chloroma or cardiac myeloid sarcoma: Case Report. Issue 8 (12th August 2019) - Abdelnabi, Mahmoud H.; Almaghraby, Abdallah; Saleh, Yehia; ElSharkawy, Eman
Abstract: Chloroma or myeloid sarcoma is rare extramedullary tumor composed of immature myeloid cells that may occur in association with or during or even before the course of adult myelodysplastic or myeloproliferative diseases. It may involve different organs including the orbit, skin, lymph nodes, bone, gastrointestinal tract, breast, central nervous system, and lung. Cardiac involvement with MS is an exceedingly rare finding. We report a very rare case of left ventricular cardiac chloroma accidentally discovered by transthoracic echocardiography (TTE) and confirmed by cardiac magnetic resonance (CMR) in an old aged male patient with acute myeloid leukemia (AML) French‐American‐British (FAB)‐class M5. Unfortunately, shortly after a prompt start of AML palliative chemotherapy protocols, the patient died due to massive intracranial hemorrhage (ICH).